Cytokine Based Immunotherapy for Cancer and Lymphoma: Biology, Challenges and Future Perspectives - Atallah-Yunes, Suheil Albert; Robertson, Michael J. (Frontiers in Immunology, 2022)
Cytokines regulate both the innate and adaptive immune responses to cancer. Although antitumor activity has been seen for several cytokines in preclinical models, they have had limited success as single therapeutic agents in clinical trials of cancer immunotherapy. However, the possible combinations of cytokines with other immune therapeutics and the advancement in genetic engineering, synthetic biology and cellular and immune therapy has led to the revival of interest in cytokines as anticancer agents. This article will review several immunostimulatory cytokines with anticancer activity, focusing on the those that have been studied in treatment of lymphoma and highlighting recent advances of potential clinical relevance.